Graphene-enhanced microwave absorption properties of Fe3O4/SiO2 nanorods. (October 2016) - Liu, Xiaofang; Chen, Yaxin; Hao, Chengcheng; Ye, Jinrui; Yu, Ronghai; Huang, Daqing
Abstract: Fe3 O4 /SiO2 /graphene composite composed of Fe3 O4 /SiO2 core–shell nanorods and graphene nanosheets were synthesized by a facile wet chemical method. Structure and morphology studies reveal that the Fe3 O4 /SiO2 nanorods with porous structure and large aspect ratio are densely wrapped by the graphene nanosheets. By changing the graphene content, the electromagnetic properties of the Fe3 O4 /SiO2 /graphene composite can be well tuned. When the weight ratio of Fe3 O4 /SiO2 to graphene reaches an appropriate value, excellent microwave absorption performance is achieved due to the large electromagnetic losses and good impedance matching. The Fe3 O4 /SiO2 /graphene composite with graphene content of 5 wt.% shows the minimum reflection loss of −27.1 dB at 12.2 GHz when the coating layer thickness is only 1.5 mm.